The interests of primary school students between traditional and digital media and their implications for their behavior from the point of view of their teachers (Journal of the College of Basic Education, 2022)
During life, man acquires knowledge, habits, skills and values that have the effect of influencing his life. He has a great role in shaping his character and shaping the future of his life. Psychologists called it the term of the formative period, in which the intelligence of man is determined and grows in a balanced and integrated development that achieves the same in the future. Researches and studies conducted in the fields of psychology, sociology, education and information also indicate the critical impact of the early stage of childhood in the formation of mental abilities, personality formation and social behavior We are living in an age of media and informational and diversity of the media. We must realize the importance of what our members of society, especially the advanced segment of children, receive. School and traditional media are no longer the sole source of information for children, but digital media in its various forms has become a powerful source of information. Children receive. As the students of the primary stage are the age group of the most important stages of intellectual construction and the best stages to acquire information and skills, whether scientific or cognitive or skilled, which is the interest of children to see everything that is new and through all the traditional media and digital, On the interests of primary school students between the traditional and digital media and their impact on their behavior through the responses of their teachers through the questionnaire directed to them and the sample of research to reach the objectives of the research. The research included three topics; the first is the systematic framework of the research, including the questions of the research problem. The second section also included the theoretical framework that included the first axis on the primary stage and its importance in shaping the individual's attitudes. In the second axis, the role of traditional and digital media in promoting public interest The third topic is the field study which was based on the survey method as the most suitable research methods for such studies using the research tool which was distributed to a sample of primary school teachers in the directorates of Baghdad education and its strength (405) teachers and teachers after the researcher ruled out (45) The results of the study showed that the percentage of primary students 'interest in traditional media (77%), while the percentage of students' primary interest in digital media (23%), in addition to the following conclusions: Most of the topics in the field of knowledge have been the impact of traditional media on the interests of primary school students more than the impact of digital mediaAffective period: The influence of traditional media has been more on students' concerns than on digital media in emotional and behavioral subjects.The field of sensory issues the effect of traditional media on the interests of primary students was more than digital media .Most of the topics affecting the interests of primary school students were within the traditional media.